Heavy metal contamination in water and fishes from the Shitalakhya river at Narayanganj, Bangladesh - Irin, Anjuman; Islam, Md Sirajul; Kabir, Md Humayun; Hoq, M Enamul (Bangladesh Journal of Zoology, 2017)
Abstract not available Bangladesh J. Zool. 44(2): 267-273, 2016